2021
DOI: 10.3389/fonc.2021.753712
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lactate Dehydrogenase Levels Display a Poor Prognostic Factor for Non-Hodgkin’s Lymphoma in Intensive Care Unit: An Analysis of the MIMIC-III Database Combined With External Validation

Abstract: BackgroundAmong the growing number of patients with hematologic neoplasms hospitalized in the intensive care unit (ICU), the largest proportion of these patients are diagnosed with lymphoma. However, less attention has been paid in the past to identifying critically ill patients and assessing the prognosis of patients in ICU. Traditional critical care-related scores have shown limitations and inaccuracy in predicting mortality risk.MethodsPatients diagnosed with diffuse large B-cell lymphoma (DLBCL) were searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 22 publications
(12 reference statements)
1
8
0
1
Order By: Relevance
“…The study demonstrated that percentages of EMAP II+CD16+, EMAPII+CD20+, and EMAP II+CD22+ cells Journal of Immunology Research had a significant positive association with elevated LDH levels, which implies the value of EMAP II expression on peripheral blood cells in NHL as a potential biomarker. The reported associations in these data support the correlation between higher levels of EMAP II expression and bad prognosis as elevated LDH levels, which are considered risk factors for poor performance and inferior overall survival [96].…”
Section: Discussionsupporting
confidence: 71%
“…The study demonstrated that percentages of EMAP II+CD16+, EMAPII+CD20+, and EMAP II+CD22+ cells Journal of Immunology Research had a significant positive association with elevated LDH levels, which implies the value of EMAP II expression on peripheral blood cells in NHL as a potential biomarker. The reported associations in these data support the correlation between higher levels of EMAP II expression and bad prognosis as elevated LDH levels, which are considered risk factors for poor performance and inferior overall survival [96].…”
Section: Discussionsupporting
confidence: 71%
“…IL-19 levels were associated with high LDH levels. High LDH levels were associated with inferior prognosis in lymphoma [ 84 ]. In the current study, patients with extranodal involvement had significantly higher IL-19 levels than patients without extranodal involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated LDH levels have also been mentioned in several studies as a diagnostic value for PCP ( 26 ). However, its predictive value for poor outcomes has rarely been reported ( 16 , 30 ). LDH has special biochemical functions.…”
Section: Discussionmentioning
confidence: 99%